“I'm in pain and I want help”: An online survey investigating the experiences of tic-related pain and use of pain management techniques in people with tics and tic disorders - Taylor, Evangeline; Anderson, Seonaid; Davies, E. Bethan (Frontiers in Psychiatry, 2022)
Objectives Tic disorders (TDs) are complex neurological conditions characterized by involuntary, persistent vocalizations and motor movements called tics. Tics involve brief muscle movements and can impair many aspects of daily functioning and quality of life in patients – and their physical nature can cause pain. Understanding individuals' experiences of tic-related pain and pain management could help explore this under-researched area and identify additional support needs for this population. The aim of this study was to investigate experiences of pain and use of pain management techniques in people with tic disorders. Methods An online survey consisting of multiple choice and open-ended questions exploring experiences of tic-related pain, help-seeking behavior for tic-related pain, and use of pain relief techniques for tic-related pain, was circulated online via international Tourette syndrome patient associations, and one online support group for Tourette syndrome. The online survey was open to adults (≥16 years) with self-reported tics. Open-ended questions were analyzed using thematic analysis. Results One hundred eighty-one participants (16–71 years; 58.0% female) from 18 countries completed the online survey. Several aspects of tics were associated with pain, including the physical effort of motor tics (n = 177, 97.8%), repetitive tics (n = 141, 77.9%) and the consequences of tics (n = 131, 72.4%). Nearly two-thirds (n = 118, 64.6%) had sought professional help for tic-related pain. Distraction techniques (n = 126, 69.6%), taking pain relief medication (n = 125, 69.1%) and altering tics (n = 111, 61.3%) were the most commonly-reported methods used to relieve and cope with tic-related pain. Thematic analysis found an interrelated complex relationship between participants' tics, pain, and pain management techniques, reflected in four themes: the “tic-pain” cycle, the impact of pain, the importance of support, and the perceived successfulness of pain management techniques. Conclusions Tic-related pain was reported to have a significant physical and psychological impact which impacted aspects of daily living in people with tic disorders. The findings add to limited research suggesting tic-related pain is a dominant issue for individuals with tic disorders, potentially impacting upon their quality of life. Increased understanding of tic-related pain and its influence may be helpful in the long-term management of tic disorders, both in terms of clinical management and patients' self-management.